PREVALENCE OF DEPRESSION AND ASSOCIATED FACTORS AMONG CAREGIVERS OF INPATIENTS AT MEDICAL AND PHARMACEUTICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Depression is a prevalent mental health issue among caregivers, especially those caring for patients with chronic conditions or requiring prolonged hospitalization. Early identification and intervention are crucial to improving both caregiver well-being and patient care quality.Objective: To determine the prevalence of depression and identify associated factors among caregivers of inpatients at the Medical and Pharmaceutical University Hospital.Methods: A cross-sectional study was conducted on 330 caregivers of inpatients at the Medical and Pharmaceutical University Hospital from December 2025 to March 2026. Depression was screened using the Patient Health Questionnaire-9 (PHQ-9) scale. Data were analyzed using descriptive statistics and multivariable logistic regression.Results: The prevalence of depressive symptoms among caregivers was 51.2%, including at-risk (22.7%), mild (9.7%), moderate (9.7%), and severe (9.1%) levels. The mean depression score was 7.5±7.2 (total: 27). Multivariable logistic regression identified several associated factors with depression as residing in rural areas (OR = 3.54; 95% CI: 1.54–8.09; p < 0.05); poor caregiver health status (OR = 2.23; 95% CI: 1.05–4.72; p = 0.036); caregiving burden (OR = 1.97; 95% CI: 1.09–3.56; p = 0.023). The type of patient illnesses was significantly associated with the depression of caregivers (p
Keywords: depression, caregivers, inpatients, PHQ-9, associated factors.